2000
DOI: 10.1034/j.1600-0765.2000.035004232.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontal pathogens in localized and generalized forms of early‐onset periodontitis

Abstract: The primary objectives of this study were to investigate the prevalence of 8 putative periodontal pathogens in subjects with early-onset periodontitis (EOP) and to evaluate the microbial differences between localized and generalized forms of this periodontal disease condition. Thirty-one females and 11 males with a mean age of 30.3 (s.d. 4.0) years were examined. Seventeen subjects had generalized (GEOP) and 25 had localized early-onset periodontitis (LEOP). Subgingival plaque samples were assayed using PCR wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
63
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 22 publications
16
63
2
6
Order By: Relevance
“…En Grecia (49), por el contrario, se observó que P. gingivalis era la bacteria más frecuentemente aislada de pacientes con periodontitis agresiva y A. actinomycetemcomitans demostró una prevalencia relativamente baja. En nuestro estudio el resultado fue similar, ya que se encontró mayor frecuencia de P. gingivalis que de A. actinomy-cetemcomitans en periodontitis agresiva, lo que coincide con lo reportado en China (3), Japón (25), Kenia (30) y Reino Unido (50). En Sur América, Cortelli (33) en Brasil y Gajardo (35) y López (37) en Chile reportaron que P. gingivalis era el microorganismo más frecuente tanto en periodontitis crónica como en periodontitis agresiva.…”
Section: Discussionunclassified
“…En Grecia (49), por el contrario, se observó que P. gingivalis era la bacteria más frecuentemente aislada de pacientes con periodontitis agresiva y A. actinomycetemcomitans demostró una prevalencia relativamente baja. En nuestro estudio el resultado fue similar, ya que se encontró mayor frecuencia de P. gingivalis que de A. actinomy-cetemcomitans en periodontitis agresiva, lo que coincide con lo reportado en China (3), Japón (25), Kenia (30) y Reino Unido (50). En Sur América, Cortelli (33) en Brasil y Gajardo (35) y López (37) en Chile reportaron que P. gingivalis era el microorganismo más frecuente tanto en periodontitis crónica como en periodontitis agresiva.…”
Section: Discussionunclassified
“…A. actinomycetemcomitans has been observed in the presence of Porphyromonas gingivalis but never in the presence of P. intermedia/P. nigrescens in early-onset periodontitis (22).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also shown PCR sensitivity and the specificity in comparison to traditional bacterial culture. 8,16 *Sensibility (positive-true) = (Number of positive samples by PCR and culture/Number of positive samples by culture) x 100 **Specificity (negative-true) = (Number of negative samples by PCR and culture/Number of negative samples by culture) x 100 VMGA: Viability maintaining microbiostatic medium In the present study, primers AA and FU had higher sensitivity for detecting A. actinomycetemcomitans but primers ASH had higher specificity (Table 3). On the other hand, when compared to culture for detecting A. actinomycetemcomitans, primers AA and FU showed similarly sensitivity (100%), which confirms their specificity.…”
mentioning
confidence: 99%